Evidence of the firm size effect in Singapore, conclusive or inconclusive? - Chua, Tai Wee (2014)
The "firm-size" effect is a well-documented anomaly in the finance literature. This paper attempts to establish whether a "firm-size" effect exists in the Stock Exchange of Singapore. Data for our research was extracted from the Financial Database of Nanyang Technological University and the local newspaper, The Straits Times. Samples of companies were collected according to the size of their market capitalization. The excess returns of each portfolio were computed and compared to that of the market excess returns for a period of five years, 1989 - 1993, on a daily basis. Based on our findings, it seemed that the excess return from each sample size was not significantly different from any other under the period of study. In conclusion, the "firm-size" phenomenon does not seem to be in existence in the local stock market.